Nutritional quality, fruit shape and relationships among exotic and local Capsicum pepper genotypes in Uganda - Asiimwe, S.; Ochwo-Ssemakula, M.; Ssekkadde, P.; Ribeiro, C.; Karungi-Tumutegyereize, J. (International Journal of Horticultural Science, 2021)
Twenty-one hot pepper genotypes comprising of local (15) and exotic (6) types (C. annuum, C. frutescens and C. chinense) were characterized for selected fruit traits after propagation in a glasshouse at the Makerere University Agricultural Research Institute Kabanyolo in Central Uganda using a completely randomized design with three replicates. Ripe fruits were harvested and analyzed; traits evaluated were all significantly different at P<0.05 with variations in quality attributes. The genotype OHA-B305-10 had the highest ascorbic acid content (128.86 mg/100 g) and is recommended for improvement of both local and exotic genotypes targeting the fresh market. Genotypes CAP0408-12 and UG2 WE0511-22, with highest total soluble solids (16.17 ºBrix) and dry matter content (28.59%), respectively should be used in improvements for industrial use or processing to products such as chilli powder or flakes. BRS-M205-04 with highest titratable acidity (1.04%) can be used in enhancing shelf life of genotypes with low titratable acids as well as for the fresh market. In spite of the intraspecific relationships among genotypes, significant differences were observed in their quantitative traits. These genotypes will, therefore, be useful in improving the quality of hot pepper fruit in Uganda.